Nonspecific Symptoms Lack Diagnostic Accuracy for Infection in Older Patients in the Emergency Department - Caterino, Jeffrey M.; Kline, David M.; Leininger, Robert; Southerland, Lauren T.; Carpenter, Christopher R.; Baugh, Christopher W.; Pallin, Daniel J.; Hunold, Katherine M.; Stevenson, Kurt B. (Journal of the American Geriatrics Society (JAGS), 2019)
Objectives To determine if nonspecific symptoms and fever affect the posttest probability of acute bacterial infection in older patients in the emergency department (ED). Design Preplanned, secondary analysis of a prospective observational study. Setting Tertiary care, academic ED. Participants A total of 424 patients in the ED, 65 years or older, including all chief complaints. Measurements We identified presence of altered mental status, malaise/lethargy, and fever, as reported by the patient, as documented in the chart, or both. Bacterial infection was adjudicated by agreement among two or more of three expert reviewers. Odds ratios were calculated using univariable logistic regression. Positive and negative likelihood ratios (PLR and NLR, respectively) were used to determine each symptom's effect on posttest probability of infection. Results Of 424 subjects, 77 (18%) had bacterial infection. Accounting for different reporting methods, presence of altered mental status (PLR range, 1.40‐2.53) or malaise/lethargy (PLR range, 1.25‐1.34) only slightly increased posttest probability of infection. Their absence did not assist with ruling out infection (NLR, greater than 0.50 for both). Fever of 38°C or higher either before or during the ED visit had moderate to large increases in probability of infection (PLR, 5.15‐18.10), with initial fever in the ED perfectly predictive, but absence of fever did not rule out infection (NLR, 0.79‐0.92). Results were similar when analyzing lower respiratory, gastrointestinal, and urinary tract infections (UTIs) individually. Of older adults diagnosed as having UTIs, 47% did not complain of UTI symptoms. Conclusions The presence of either altered mental status or malaise/lethargy does not substantially increase the probability of bacterial infection in older adults in the ED and should not be used alone to indicate infection in this population. Fever of 38°C or higher is associated with increased probability of infection. J Am Geriatr Soc 67:484–492, 2019.